PERTANGGUNGJAWABAN PIDANA ANAK YANG BERKONFLIK DENGAN HUKUM DALAM TINDAK PIDANA PENYALAHGUNAAN NARKOTIKA - Sembiring, Junior Kadiva; Ramadani, Suci; Hasibuan, Aulia Rahman Hakim (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: This study examines the criminal liability of children in conflict with the law in the context of drug abuse crimes. The main focus of this study is to identify the legal aspects that regulate the liability of children, as well as the challenges faced in enforcing the law against child offenders. The methods used consist of normative legal analysis and interviews with legal practitioners, psychologists, and social workers. specific provisions in the Child Criminal Justice System Law, implementation in the field is often hampered by social stigma, lack of rehabilitation facilities, and public misunderstanding of children's rights. This study recommends the need for policy reform and increased public awareness of child protection, as well as a rehabilitative approach.Keyword: Criminal Liability, Children, Drug Abuse.